GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGAMBIL KEPUTUSAN - Muhammad Affandi; Muchammad Eka Mahmud; M Kusasi (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
The background of this research is the principal's leadership style in implementing his leadership in making decisions. The purpose of this study was to find out how the principal's leadership style in making decisions and how the process of taking and the basics in making decisions and the obstacles that occur when making decisions in high school institutions throughout the city of Samarinda. The type of this research is phenomology qualitative research, with data collection techniques of observation, interviews and decomentation. Data analysis techniques in the form of data condensation and data validity test. The objects of this research are principals, vice principals and educators as well as education staff throughout the city of Samarinda. The results showed: (1) that the principal's leadership style in making decisions is a charismatic leadership style used by the principal of SMA Negeri 5 Samarinda while SMA Islam Bunga Bangsa has a democratic leadership style, (2) the process of making decisions by involving teachers and some teachers, with the basic process of making decisions by the principal of SMA Negeri 5 Samarinda and SMA Islam Bunga Bangsa by involving intuition and the opinions of other parties, models in making decisions using data and facts in making decisions. (3) the inhibiting factor in making decisions is the difference in character and the rules that sometimes do not match between the SMA Negeri 5 Samarinda school and the education office of the province of East Kalimantan, while the inhibiting factor at SMA Islam Bunga Bangsa is due to the density of activities at school, intra-curricular activities schools, foundation activities and activities with external institutions at the same time, besides that the inhibiting factor is the individual character of teachers and school staff in completing the tasks given by the principal of SMA Islam Bunga Bangsa.